(untitled) (Global Journal of Science Frontier Research, 2023)
Introduction High-throughput sequencing facilitates the diagnosis of Usher syndrome and other conditions involving deafness and blindness that are genetically related with improvements not only in accurate diagnosis time savings and genotype-phenotype correlation Advances in genomic sequencing also makes it possible to approach isolated or remotely located populations with community genetics methodologies Material and methods A remotely located and highly endogamic family with Usher syndrome with four affected members were ascertained with USH by one ophthalmologist and several undergraduate medical students Eye fundus diagnostic and audiometry tests were made to the index patient Following an informed consent adapted application several family members were sampled for WES analysis The sequencing and detection of variants was also performed from the sample of affected patients and from five healthy relatives by means of a multigenic panel based on exome